Private Higher Education in Vietnam: Issues of Governance and Policy - Nguyen, Dao T. H. (International Higher Education, 2016)
Among many issues facing private higher education (PHE) in Vietnam, governance tensions and irrelevant government policy are widely considered as the most pressing ones. They are impediments to survival and development of private universities. In order to provide most reliable and viable recommendations, the researcher conducted a qualitative multi-site case study with the instrumentation of in-depth semi-structured interviews and document analysis to explore each issue and trace the fundamental causes from legislation. The internal governance tension emerged from conflicting viewpoints among members of the board of directors and president about whether to run their institutions as not-for-profit or for-profit. Misleading legislation has resulted in this tension and confusion in the conceptions of the two categories in practice. The external governance tension was found in the relationship between the government and individual institutions. There have been many complaints about impractical, irrational, inconsistent, and fluctuating legislation governing private institutions. Educational policy was also problematic with its limited resources and unequal treatment toward PHE.